Pentagon Fraud Analysis in Detecting Fraudulent Financial Reporting Using the Fraud Score Model - Roza Mulyadi; Fita Rani Aulia; Mega Arum (PT. EQUATOR SINAR AKADEMIA, 2021)
This study was conducted to determine the effect of pentagon fraud (pressure, opportunity, rationalization, capability and arrogance) in detecting fraudulent financial reporting using F-Score in financial companies listed on the Indonesia Stock Exchange in 2017-2019. Using associative quantitative research methods. The population of this study are 100 companies with 49 sample of companies for 3 periods, so the sample total is 147 samples was obtained which was taken by purposive sampling technique. The testing method of this research is through multiple regression analysis with the SPSS 22 program. The results of the partial test analysis show that pressure and opportunity has significant effect in detecting fraudulent financial reporting. Whereas rationalization, capability and the arrogance variable has insignificant effect in detecting fraudulent financial reporting. The test results simultaneously are pressure, opportunity, rationalization, capability and arrogance has significant effect in detecting fraudulent financial reporting.